Kajian Sosial Intelektual K.H. Ahmad Dahlan Dan Kontribusinya Dalam Menggerakkan Pendidikan Islam - Purwanto, Haris (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
ABSTRACTThis study aims to examine the social and intellectual thought of K.H. Ahmad Dahlan and his contribution to advancing Islamic education through the Muhammadiyah movement. The research employs a qualitative descriptive method with a social phenomenology approach to understand Dahlan's ideas and their impact on educational reform. Data were collected through document analysis and literature review related to the historical background and intellectual contributions of K.H. Ahmad Dahlan. The results show that K.H. Ahmad Dahlan successfully integrated religious knowledge with general knowledge, creating a more progressive model of Islamic education. One of his major contributions was opening access to education for marginalized groups, particularly women and the poor, who had previously been overlooked by traditional education systems. Furthermore, Dahlan played a key role in establishing Muhammadiyah schools across Indonesia, which acted as a driving force for modern Islamic education. His balanced approach between spirituality and intellectuality contributed to educational reform that encompassed both religious studies and modern knowledge, adapting to the needs of contemporary society. This contribution had a significant influence not only in Indonesia but also inspired Islamic education systems in other countries. Dahlan's thought remains relevant today, continuing to shape the development of Islamic education in the era of globalization.Keywords: K.H. Ahmad Dahlan, Islamic education, contribution social